Remote Implementation Of Laboratory Works - Modern Approach - A.Bychkov (Kherson State University, 2009)
The question of providing the remote access to implementation of laboratory works is examined. Creation of such system requires realization of such functions: simulation of laboratory equipment, start of virtual laboratory works, remote connecting to the operating laboratory equipment.